2010
DOI: 10.1002/ddr.20362
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial protein kinase inhibitors

Abstract: Protein kinases have become the second most important group of drug targets for the pharmaceutical industry next to G-protein-coupled receptors. Thus, over the past decade, a significant number of small molecules have been generated for protein kinase drug optimization programs. The vast majority of kinase inhibitors target the ATP binding site of the enzyme; however, the poor protein kinase selectivity of ATP-competitive protein kinase inhibitors (PKIs) limits their use for treating chronic diseases. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 104 publications
0
34
0
3
Order By: Relevance
“…In this regard, the future advancement of the field of prokaryotic PTMs will also be discussed, as a better understanding of these signaling systems will shed light on how eSTK/Ps empower bacteria to cause a range of infections in most important pathogens, and could ultimately offer a realistic focal point of therapeutic strategies in disease prevention. [74][75][76][77]146 Transcription Factors Regulated by eSTKs and eSTPs…”
Section: 66mentioning
confidence: 99%
“…In this regard, the future advancement of the field of prokaryotic PTMs will also be discussed, as a better understanding of these signaling systems will shed light on how eSTK/Ps empower bacteria to cause a range of infections in most important pathogens, and could ultimately offer a realistic focal point of therapeutic strategies in disease prevention. [74][75][76][77]146 Transcription Factors Regulated by eSTKs and eSTPs…”
Section: 66mentioning
confidence: 99%
“…It was found that congeners of pyrazolo [2,3-b] quinoline have inhibitory activity on several ESTK from several species with wide ranging activity and relatively low specificity. For example, CID 665826 (1) and related compounds reveal inhibitory activity on GSK-3, CDK and ATM kinases 6 . Compound 2 built on the 1H-pyrazolo [3,4-b]pyridine fragment showed inhibition on disease-relevant protein kinases DYRK1A, CDK5 and GSK 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, some BSTK are involved in virulence of Mycobacteria and resistance of Streptomyces to aminoglycoside antibiotics 2,3 . Since it is evident that BSTK play an indispensable role in some prokaryotic organisms, these protein kinases are considered as attractive antibacterial drug targets 1,4 . It was also shown that protein kinase inhibitors of eukaryotic serine/threonine protein kinase(s) (ESTK) could be active against some BSTK 1,4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations